2019
DOI: 10.1371/journal.pone.0207045
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of “dialysis adequacy” as an outcome in randomised trials conducted in adults on haemodialysis

Abstract: BackgroundClinical trials are most informative for evidence-based decision-making when they consistently measure and report outcomes of relevance to stakeholders, especially patients, clinicians, and policy makers. However, sometimes terminology used is interpreted differently by different stakeholders, which might lead to confusion during shared decision making. The construct dialysis adequacy is frequently used, suggesting it is an important outcome both for health care professionals as for patients.Objectiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 73 publications
1
16
0
2
Order By: Relevance
“…While there is a vast body of research on dialysis outcomes, 15 19 our findings are novel in their focus on the transitioning experience when changing KRT modality. To our knowledge, this is the first study to use a truly inductive method to understand the process of transitioning between the different KRT modalities.…”
Section: Discussionmentioning
confidence: 90%
“…While there is a vast body of research on dialysis outcomes, 15 19 our findings are novel in their focus on the transitioning experience when changing KRT modality. To our knowledge, this is the first study to use a truly inductive method to understand the process of transitioning between the different KRT modalities.…”
Section: Discussionmentioning
confidence: 90%
“…The reason is that Kt/V and URR alone are not sufficient to evaluate dialysis adequacy. Querying the well-being and quality of life of the patient is therefore extremely important in the evaluation of dialysis adequacy (Steyaert et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The Kt/V values of patients experiencing muscle cramps were interestingly found to be statistically significantly higher than the others in our study. An interview conducted by Steyaert et al (2019) with 11 patients revealed that only one patient described dialysis adequacy as removal of toxic products from the blood while the others thought their actual survival was due to adequate dialysis. Two patients attributed muscle cramping to high ultrafiltration and emphasized that this could be prevented by strict fluid control while good dialysis could be provided with low ultrafiltration.…”
Section: Discussionmentioning
confidence: 99%
“…The need to use patient relevant rather than biochemical surrogates as outcomes of clinical studies has recently gained a lot of attention [4,5]. Various studies aimed to identify a gold quantifier of uremic burden that is associated with hard endpoints such as Quality of Life (QoL), morbidity, and mortality [8].…”
Section: Discussionmentioning
confidence: 99%
“…By using these models, a conceptual association between composite uremic load and other outcomes can be examined. Second, several initiatives have emerged pointing to the necessity to use patient relevant rather than pure surrogate (biochemical) markers as outcomes in studies [4,5]. Survival is of course important, but it does not allow to assess the impact of alternative strategies in a short time frame.…”
Section: Introductionmentioning
confidence: 99%